Recovery of dietary fiber and polyphenol from grape juice pomace and evaluation of their functional properties and polyphenol compositions. Issue 1 (3rd January 2017) - Zhang, LuLu; Zhu, MengTing; Shi, Ting; Guo, Cong; Huang, YouSheng; Chen, Yi; Xie, MingYong
Abstract : Our results indicated that the phenolic composition is essential for the antioxidant activity of "antioxidant dietary fiber (ADF)". Abstract : The present work aimed at the recovery and characterization of dietary fiber and polyphenolic compounds extracted from red grape pomace, a by-product generated after grape fruit processing. High contents of total DF were found in the dietary fiber extracts (57.24%), whereas insoluble fiber was the major fraction (51.70%). And it showed good functional properties, including swelling capacity (4.01–8.32 mL g −1 ), water holding capacity (1.91–4.23 g g −1 ) and oil holding capacity (0.59–0.65 g g −1 ). After separation from the dietary fiber, phenolic extracts with high concentrations of total phenolic compounds and total flavonoids, showed high antioxidant activities, while the separated dietary fiber showed little antioxidant activities. This indicated that the phenolic composition is essential for the antioxidant activity of "antioxidant dietary fiber (ADF)". The identification of individual polyphenols was performed applying the HPLC-ESI-MS/MS technique and 31 compounds have been identified belonging to 4 groups, including anthocyanins, flavonols, flavan-3-ols and phenolic acids. Based on this study, we believe grape juice pomace could potentially be exploited as an inexpensive source of natural dietary fiber and phenolics and possibly used as a functional food ingredient.